PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PERMAINAN GOBAK SODOR BERBASIS KEARIFAN LOKAL DI SEKOLAH DASAR - Novi Octaviani; Iis Nurasiah; Irna Khaleda Nurmeta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Problems Students have difficulty understanding and solving problems related to adding and subtracting fractions. The reason is that students are less active and enthusiastic in participating in learning and the teaching and learning process is monotonous so that it is less varied and innovative. Therefore, this research is a PTK, the aim of this research is to find out the activities of educators, through the traditional game gobak sodor which is one option to improve the learning outcomes of class V students at SDIT Darussalam. The results of this research show that before the action was taken, only 39% of students completed their learning outcomes with an average score of 61. After the action was taken in cycle I, student learning outcomes increased to 60% with an average score of 68 and in cycle II this happened again. The percentage increase in student learning outcomes became 80% with an average score of 79. So it can be concluded that the application of the traditional game Gobak Sodor is able to help students achieve optimal learning outcomes in Mathematics.